“There is no such thing as Dian cuisine!” Food and local identity in urban Southwest China - Klein, Jakob A. (Food & History, 2013)
Abstract The article asks why it is that projects celebrating regional cuisine may be unsuccessful in gaining recognition from people in the region. It explores how a recent campaign in Yunnan, China attempted to construct a “modern” image for the province through promoting a distinctive, “green” regional cuisine. However, in a context of rapid changes to urban space and the food supply, residents in the provincial capital, Kunming, were ambivalent towards the notion of a regional cuisine. It is argued that to gain recognition locally, public celebrations of regional cuisine must resonate with people’s lived experiences and performances of “their” foods.